Crime and fear in public places: towards safe, inclusive and sustainable cities - Ceccato, Vania; Nalla, Mahesh (Routledge studies in crime and society, 2020)
PART I -- Crime and fear in public places: An Introduction Chapter 1. Crime and fear in public places: Aim, scope, and context Chapter 2. The circumstances of crime and fear in public places: A Review of theories Chapter 3. The architecture of crime and fear of crime: Research evidence on lighting, CCTV and CPTED features PART II -- The environment Chapter 4. Do green areas affect crime and safety? Chapter 5. Safety of urban park users: The case of Poznań, Poland Chapter 6. The role of public places in Disability Hate Crimes (DHC) PART III -- The movement Chapter 7. Youth safety in public transportation: The case of Eastern Mexico City, Mexico Chapter 8. Transit safety among college students in Tokyo/Kanagawa, Japan Chapter 9. Women and LGBTI youth at target: Assessing transit safety in Rio Claro, Brazil Chapter 10.